The psychological foundations of evidence law - Saks, Michael J. (Psychology and the law, 2016)
Introduction : the crossroads of psychology and evidence law -- Part I. Minding the jury -- Judges versus juries : trying the facts -- Balancing acts -- Instructions to disregard and to limit use -- Part II. Judging the witness -- Witness the witness -- Character evidence : propensity and impeachment -- Part III. Other types of evidence -- Hearsay and exceptions -- Scientific and other expert evidence -- Conclusion: The lessons of psychology for evidence law -- Appendix A: Table of concepts -- Appendix B: Federal Rules of Evidence (abridged)